Influence of Agroforestry Technology Adoption on Poverty Reduction Among Farming Households in Okunland of Kogi State, Nigeria - Oke, D. O.; Adisa, S. A.; Obafunsho, E. O.; Ojedokun, C. A.; Oyetoki, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2024)
The significance of Agroforestry to the enhancement of livelihoods of farming households, through its contribution to food and income security as well as the improvement of crop productivity of farmers, cannot be overemphasized. Consequent upon this, the study assessed the impact of agroforestry practices on poverty reduction among small farming families in Okunland, Kogi State, Nigeria. In selecting respondents for the study, a multi-stage sampling approach. This study used descriptive statistics and inferential statistics for analysis. The descriptive statistics used are frequencies and percentages, while the inferential statistics used is Foster Greer Thorbecke (FGT) technique. Findings showed that about 35% of those who adopted the practice of agroforestry did not measure up to the poverty line (N54, 520.13k). Therefore, since they were found below the poverty line, they were regarded as poor. For those who did not adopt the practice of agroforestry, sixty seven percent of them were found below the poverty line (N31, 654.19k). By implication, this category of people can be regarded as poor. In order to reveal the extent of poverty among the respondents, FGT poverty index was used. Results from this therefore showed that the farming households who adopted and practiced agroforestry technology had a better livelihood when compared to those that failed to adopt the technology. In addition, it was discovered from the study that several constraints were militating against the adoption of agroforestry technologies by the farming households in the study area. Some of the constraints were lack of knowledge and required skills on agroforestry, long gestation period of trees, insufficient land for tree planting, lack of planting materials among others. Consequent upon this, this study recommends that necessary efforts should be made by government and concerned stakeholders to increase the adoption of agroforestry technology by creating awareness and sensitizing farmers on significance of adopting agroforestry technology and the associated benefits derivable from agroforestry practices. To accomplish this, extension agents and subject matter specialists on agroforestry should train and enlighten farmers on how best to use their land so as to accommodate both arable and tree crops so as to ensure improved productivity.